2021
DOI: 10.1002/smll.202007803
|View full text |Cite
|
Sign up to set email alerts
|

Designing Flexible but Tough Slippery Track for Underwater Gas Manipulation

Abstract: Lubricant‐infused slippery surface exhibits a series of superior properties such as pressure tolerance, self‐healing, oil‐repellence, etc. Especially when being applied in an aqueous environment, the reliable bubble manipulating ability of slippery surface offers great opportunities to develop advanced systems in the field of gas transport, water splitting, etc. To improve the strength and the functionality of slippery surfaces, a sliced lubricant‐infused slippery (SLIS) track is presented here, possessing bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 50 publications
(15 reference statements)
0
36
0
Order By: Relevance
“… 41 Finally, we show the possibility to fold thin sheets underwater into three-dimensional structures using the capillary adhesiveness of air bubbles, overcoming the elastic bending energy of the surface. 42 , 43 …”
Section: Introductionmentioning
confidence: 99%
“… 41 Finally, we show the possibility to fold thin sheets underwater into three-dimensional structures using the capillary adhesiveness of air bubbles, overcoming the elastic bending energy of the surface. 42 , 43 …”
Section: Introductionmentioning
confidence: 99%
“…The single bubble, meanwhile, could slide easily with an ultralow contact angle hysteresis due to the inert slippery liquid interface . As a more reliable and stable bioinspired functional wetting surface, SLIPS with a broad prospect of gas bubble and droplet manipulations have attracted the attention of researchers. For example, Yu et al reported directional bubble transport on the single crook-shaped SLIPS track . Li and Guo investigated the evolution of bubble shapes on stripe-shaped SLIPS and found that the bubble shapes changed during the directional transport on a wedge-shaped slippery surface .…”
Section: Introductionmentioning
confidence: 99%
“…Realizing flexible manipulation of bubbles is crucial for both academic research and industrial settings, such as gaseous microreactions, organic degradation, sewage treatment, undersea gas mining, hydrogen production, and biological respiration. , Conventional strategies of bubble control are mainly based on the assistance of buoyancy, or the cooperation of wetting driving force and the Laplace pressure generated from substrate’s morphology. For instance, Jiang et al proposed a Janus membrane for unidirectional penetration of underwater bubbles by femtosecond laser-assisted ablation and nanoparticle deposition . Yu et al reported a sliced lubricant-infused slippery track that could cooperatively possess flexibility and toughness for reliable bubble manipulation . Recently, it has been reported that smart stimuli-responsive functional surfaces (e.g., light, magnetic field, heat) are frequently reported in bubble manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Gas bubbles are ubiquitous in natural environments and living organisms. Realizing flexible manipulation of bubbles is crucial for both academic research and industrial settings, such as gaseous microreactions, 1 organic degradation, 2 sewage treatment, 3 undersea gas mining, 4 hydrogen production, and biological respiration. 5,6 Conventional strategies of bubble control are mainly based on the assistance of buoyancy, 7−10 or the cooperation of wetting driving force and the Laplace pressure generated from substrate's morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation